The White Spot Syndrome Virus (WSSV): a review and its impact on Costa Rican shrimp production - Varela Mejías, Alexander (2013)
A brief review is presented on the White Spot Syndrome Virus (WSSV), the main disease affecting shrimp farming worldwide due to its economic and productive effects. The review describes the beginnings of WSSV as well as early reports on shrimp crops in Asia and how it spread to other productive areas. In addition, it includes a non-exhaustive list of some of the species susceptible to WSSV infection, an ultramicroscopic description of the causal agent, symptomatology shown by infected animals, and the most important diagnostic techniques. The main cytopathic effects are also described. Finally, this paper includes some factors that may trigger WSSV disease outbreaks, the impact of this virus in Costa Rica, its distribution, as well as some of the current alternatives for its mitigation.